WUJUD CAMPUR KODE POSTINGAN AKUN FACEBOOK MEME MANADO BASUDARA - Mamudi, Matrona; Tulung, Golda J.; Pandean, Mariam (Kajian Linguistik, 2019)
AbstractThis researchaims to describe mixing code form of the post of facebook account Meme Manado Basudara. The object of this research mixing code form of the post of facebook account Meme Manado Basudara. The research method used is descriptive qualitative method. Data analysis techniques in this research are descriptive analysis and data collection techniques with 2 techniques, namely reading and note taking. Based on the analysis of the research, it was found that the forms of words consisting of nouns (nouns), adjectives (adjectives), verbs (verbs), adverbs (adverbs). The various forms of phrase codes were also found in this research, namely noun phrases, verb phrases and adjective phrases.There are mixing code form of words consisting of mixed forms of noun code (nouns) instead of 7 nouns consisting of 6 Indonesian nouns and 1 English noun. The mixing code form of adjective found 8 adjectives consisting of 6 Indonesian adjectives, 6 Indonesian adjectives and 2 English adjectives. The mixing code form of verbs (11 verbs), 11 verbs consisting of 6 Indonesian verbs, 5 verbs in English. The form of a mixture of adverb code that is 3 Indonesian adverb languages. The results of the research mixing code form of the post of facebook account Meme Manado Basudaraalso found mixed forms of phrase codes including 1 English noun phrase, 1 English verb phrase and 1 English adjective phrase.Keywords : mixed code, social media, ,meme